Hsa_circ_0024093 accelerates VSMC proliferation via miR-4677-3p/miR-889-3p/USP9X/YAP1 axis in in vitro model of lower extremity ASO - Xue Zhang; Peng Wang; Kai Yuan; Maoran Li; Yiting Shen; Huafa Que; Yunfei Wang; Wei Liang (Elsevier, 2021)
Arteriosclerosis obliterans (ASO) of the lower extremities is identified as a kind of cardiovascular disease with aberrant proliferation and apoptosis of vascular smooth muscle cells (VSMCs). Accumulating studies have demonstrated the vital role of Yes1-associated transcriptional regulator (YAP1) in VSMCs, while its upstream regulatory mechanism in VSMCs in ASO of the lower extremities needs to be further elucidated. Herein, hsa_circ_0024093, a circular RNA (circRNA) from YAP1, was identified to positively regulate the protein level of YAP1 in VSMCs. Functionally, silencing of hsa_circ_0024093 obviously impeded cell proliferation and migration and promoted apoptosis in VSMCs in the in vitro model of ASO of the lower extremities. Mechanistically, it was found that hsa_circ_0024093 could regulate the expression of USP9X, which further induced YAP1 deubiquitination to stabilize YAP1 protein. In depth, it was revealed from mechanism experiments that hsa_circ_0024093 sequestered miR-889-3p or miR-4677-3p to enhance USP9X expression. Further, rescue assays validated that hsa_circ_0024093 regulated the miR-4677-3p/miR-889-3p/USP9X axis to accelerate the proliferation and migration of VSMCs in the in vitro model of ASO of the lower extremities. These findings may provide a novel perspective for better understanding of ASO of the lower extremities.